Effect of LST parameter on surface morphology of modified copper substrates - Siti Faqihah, Roduan; Juyana, A. Wahab; Mohd Arif Anuar, Mohd Salleh; Nurul Aida Husna, Mohd Mahayuddin; Aiman, Mohd Halil; M., Ishak (Malaysian Tribology Society (MYTRIBOS), 2020)
This study aimed to investigate the effect of laser surface texturing (LST) parameter on the surface morphology of copper substrate. The results of different loop number (L1 to L5) on the resolidified material of micro-dimpled surface modified copper substrate were examined. The micro-dimple with a diameter of 100 μm was produced via LST process by varying the dimple distance at 100 μm and 180 μm. The resolidified material that was formed after the surface texturing process was analysed using 3D measuring laser microscope. Based on the data collected, the dimple was successfully engraved on the copper substrate. The increasing number of loop increase the quantity of the melted material which lead to higher amount of resolidified material and surface roughness.